MANAGEMENT DECISION-MAKING IN ACTIVITY OF PUBLIC AUTHORITIES: WORLD EXPERIENCE ANALYSIS - Tereshchenko D.A. (Pressing Problems of Public Administration, 2018)
The theoretical substantiation of objective prerequisites for management decision-making in the public authority systems of foreign countries is carried out. Рossible directions of adaptation of foreign experience of work with information in the processes of development and adoption of managerial decisions are proposed.